Cascaded Brillouin fibre lasers coupled to unitravelling carrier photodiodes for narrow linewidth terahertz generation. Issue 9 (1st April 2014) - Ducournau, G.; Bacquet, D.; Szriftgiser, P.; Pavanello, F.; Peytavit, E.; Zaknoune, M.; Beck, A.; Lampin, J.‐F.
Abstract : Narrow linewidth terahertz (THz) generation using a cascaded Brillouin fibre laser structure and a unitravelling carrier photodiode is investigated. Using two distributed feedback lasers separated by > 1 THz with 1 MHz initial linewidth, the use of the cascaded Brillouin laser greatly increases the linewidth reduction factor compared to a single Brillouin laser structure. The linewidth of the realised THz source is found to be < 100 Hz at 1014.7 GHz without the use of any active stabilisation of the laser cavity or any microwave reference.